Iran and the European Union after the Nuclear Deal - Radosław Fiedler (CES Working Papers, 2018)
This article is focused on relations between the European Union and Iran after the Joint Comprehensive Plan of Action (JCPOA). The nuclear deal gave Iran a unique chance for developing cooperation with the EU. There are challenges to this, such as the Iranian autocratic system, its violation of human rights, its regional ambitions which threaten stability and, last but not least, the United States' unilateral withdrawal from the JCPOA. The failure of the EU's policy towards Iran might have negative consequences for regional security. This article presents both the potential benefits and problems in relations between Iran and the EU.
Keywords: 330; European Union; Iran; nuclear deal; sanctions; foreign policy